Improving the Orbit Injection Accuracy of a Launch Vehicle by Using a Mode-Switching Strategy for a Dual-Axis Rotational Inertial Navigation System - Jun Li; Shifeng Zhang; Zhenlin Ma (Sensors)
Due to a short flight time, the dual-axis rotational inertial navigation system carried by some launch vehicles or missiles is often only used for self-calibration and self-alignment. It is generally in the strap-down state rather than the rotation modulation state during flight. This wastes the precision potential of the navigation system. Therefore, a mode-switching strategy is proposed in this paper to improve the orbit injection accuracy of a launch vehicle. The rotational navigation system of the launch vehicle is in the near-platform mode or strap-down mode at different periods. It is switched in a timely manner to take advantage of the various modes. Numerical simulation and turntable experiment results show that compared with the traditional strap-down inertial mode, the mode-switching strategy can effectively improve the orbit accuracy of the launch vehicle by about 12% to 13% and hardly increases any costs.